The Effect of Teaching Therapic Interventions on the Tolerability of Disappointed Mothers with Autism Child (European Journal of Behavioral Sciences, 2018)
The aim of this study was to examine the effect of teaching therapic interventions on the tolerability of disappointed mothers with autism children. The sample included 50 mothers with autism child that they were selected by random sampling and divided into 2 control and treatment groups. Tolerability and teaching therapic interventions questionnaires were used to collect data. Pearson correlation coefficient and covariance analysis were used to analyze data. The result showed that there is a significant relationship between therapic interventions and tolerability.